Physicochemical parameters and microbiological quality of water from local fish farm - Foo, Tun Xian. (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The outbreak of fish disease has threatened the development of aquaculture industry in years. Enterobacteriaceae is a member of gram-negative bacilli and contain more than 30 genera. They act as the main indicator for the bacteriological water quality. The study was conducted at Malaysian Mahseer breeding farm near Asajaya to determine the physicochemical parameter and occurrence of Enterobacteriaceae family in fishes in the ponds which this could reflect the healthiness of water. Water sample were collected from the ponds and analyzed for the presence of Enterobacteriaceae. Samples were plated on MacConkeyagar and colonies formed were further testes by 'String Test'. Gram-negative colonies were analyzed with (GTG)s PCR. The phylogenetic tree was constructed based on the DNA banding pattern from the (GTG)5 PCR. Suspicious species were identified using API 20 E Diagnostic Kit. Four major clusters were shown in the dendrogram indicate the diversity of the bacteria strains. Twelve strains of Escherichia coli, four strains Serratia odorifera, one strain of Serratia liquefaciens and eight strains of Aeromonas hydrophila/caviae/sobria were detected.